Community capacity building towards a sustainable community based ecotourism development: a case study on Orang Asli Hulu (Jakun) In Kampung Selai, Bekok, Johor, Malaysia - Mohd Noh, Ahmad Nahri (2021)
The major focus of this research is to find a better and more sustainable module to develop tourism in Malaysia. As current mass tourism module, though lucrative, is not socially and environmentally sustainable. There is a need for a new module for tourism in Malaysia. This thesis seek to explore the potential of using Community Capacity Building (CCB) as a tool to develop a sustainable Community Based Ecotourism (CBET) within the community of Orang Asli Hulu (Jakun), in Kampung Selai, Bekok, Johor. With their close proximity to Taman Negara Johor, Endau-Rompin, the research site is a prime location for tourism. However, literatures and on-ground reports show that there has been no development for tourism introduced to the community. Using semi-structured interview as instrument to gather data from 15 participants, both from the stakeholder and community sides, the research revealed that the basic dimensions of CCB for tourism; participation, knowledge, communication and leadership plays an important part for a sustainable CBET development. The research also manages to uncover a new dimension; exposure, that is crucial in order to develop any tourism development in an Orang Asli community. Given their rural geographic and cultural factors. From the results, the ‘community’ level within the CCB framework was most impacted, by any CCB programs for tourism in the area. Specific factors for CBET development in the area are also listed and discussed. Along with recommendations for future research and CBET development plans for the area, grounded on the findings of this research. With this, the researcher hoped that the community of Kg. Selai can manage themselves to create a sustainable CBET, with the right help and push from stakeholders, and ultimately promote a better, a more sustainable and less destructive way to develop tourism in Malaysia.